2013
DOI: 10.1016/j.nicl.2013.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal subfield volumetry in mild cognitive impairment, Alzheimer's disease and semantic dementia

Abstract: BackgroundHippocampal atrophy is a well-known feature of Alzheimer's disease (AD), but sensitivity and specificity of hippocampal volumetry are limited. Neuropathological studies have shown that hippocampal subfields are differentially vulnerable to AD; hippocampal subfield volumetry may thus prove to be more accurate than global hippocampal volumetry to detect AD.MethodsCA1, subiculum and other subfields were manually delineated from 40 healthy controls, 18 AD, 17 amnestic Mild Cognitive Impairment (aMCI), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
231
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(257 citation statements)
references
References 53 publications
16
231
4
2
Order By: Relevance
“…Recent studies have highlighted the apparent paradox of episodic memory performance in SD, whereby everyday memory is relatively preserved (Adlam, et al, 2009;Irish, et al, 2011) despite severe hippocampal atrophy often comparable to, or even greater than, that typically observed in AD (Chan, et al, 2001;Davies, et al, 2004;Galton, et al, 2001;La Joie, et al, 2013;Nestor, et al, 2006). While the hippocampus arguably occupies a crucial node in the classic episodic memory network (reviewed by Dickerson & Eichenbaum, 2010), our findings suggest that the hippocampal atrophy found in SD does not, by default, give rise to a global amnestic profile.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Recent studies have highlighted the apparent paradox of episodic memory performance in SD, whereby everyday memory is relatively preserved (Adlam, et al, 2009;Irish, et al, 2011) despite severe hippocampal atrophy often comparable to, or even greater than, that typically observed in AD (Chan, et al, 2001;Davies, et al, 2004;Galton, et al, 2001;La Joie, et al, 2013;Nestor, et al, 2006). While the hippocampus arguably occupies a crucial node in the classic episodic memory network (reviewed by Dickerson & Eichenbaum, 2010), our findings suggest that the hippocampal atrophy found in SD does not, by default, give rise to a global amnestic profile.…”
Section: Discussionmentioning
confidence: 48%
“…On close inspection, however, a paradox becomes apparent when we consider that SD patients display a relatively intact capacity for new learning and episodic retrieval in the context of marked hippocampal atrophy. Converging evidence reveals that the hippocampus is unequivocally involved in the SD pathological process and atrophy in this region can even surpass that typically seen in AD (Chan, et al, 2001;Davies, Graham, Xuereb, Williams, & Hodges, 2004;La Joie, et al, 2013), yet SD patients display substantially intact episodic memory (reviewed by Hodges & Patterson, 2007). The disease syndromes differ, however, in terms of the rostral-caudal gradient of hippocampal atrophy, with anterior portions most affected in SD versus predominantly posteromedial involvement in AD (Ranganath & Ritchey, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible that the hippocampus does not atrophy uniformly during the tAD disease course. Indeed, previous studies have shown that the CA1 subfield is disproportionately affected in early AD [Ch etelat et al, 2008;Csernansky et al, 2005;La Joie et al, 2013;Mueller et al, 2010;Pluta et al, 2012;Wang et al, 2006] and that hippocampal subfields or hippocampal shape may be more sensitive at distinguishing MCI or very mild AD subjects from controls than whole-hippocampal volume [Csernansky et al, 2005;La Joie et al, 2013;Mueller et al, 2010;Pluta et al, 2012]. Therefore, SPHARM coefficients may prove to be more useful at distinguishing controls from tAD at an earlier disease stage.…”
Section: Discussionmentioning
confidence: 99%
“…The HP formation contains subfields with distinct neuronal cell types and specialized connectivity subserving learning and memory, visuospatial functions and other cognitive modalities [6,7]. Findings indicate that subtle pathological changes within the HP may precede global HP atrophy [8,9,10,11], and these substructures may be sequentially affected according to an anterior to posterior gradient of vulnerability [12]. Specifically, atrophy should first be evident in HP input structures, such as the ERC, before a regional atrophic pattern including the HP head, body and tail follows [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent findings indicate that the HP cornu ammonis sector 1 (CA1) region is one of the earliest affected regions in MCI patients [8,11,14]. One study found atrophy of the CA1 in combination with the subiculum to be associated with later amnestic MCI (aMCI) classification.…”
Section: Introductionmentioning
confidence: 99%